Parents' jurisdiction in marriage : a comparative juristic study with reference to Malaysian context - Siti Norazian Razali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
Islam as a comprehensive code regulates all aspects of human life. At personal level it orders marriage as an alternative to sexual promiscuity. To realize this objective, it ordains close relatives to actively participate in the marriage choice of their women folk and its conclusion. Nevertheless, due to the inroad of Western liberal cultures, this aspect of Islamic law has been somewhat misconceived and neglected by some parents today. Accordingly, this study is designed to find the reasons for this attitude among some segments of the Malaysian society. To this end, the researcher conducted a survey of opinions though a questionnaire given to 240 parents in the state of Selangor. The findings seem to confirm this assertion. Using both qualitative and quantitative methods to analyze the data, the study found several reasons: firstly, most of the parents think that parental jurisdiction is merely ceremonial by consenting or withholding it during wedlock. Secondly, a great majority think that it is not wrong for Muslim girls to get involved in pre-marital romantic relationship in their search for prospective husbands. Thirdly, some parents even think that educated girls can freely go about finding their own husbands though their parents still need to endorse their final choice. Lastly, Malay girls culturally make their choice of life partner on their own. This means that they do not ask their parents to find their marriage partner. While agreeing with the freedom of marriage for such girls, I disagree with the idea of exercising it without observing ethical limits of the Shari'ah. Accordingly, what is needed is educating Muslim parents to exercise effective and not official authority if we are desirous of creating a clean and righteous ummah.